DOES MUTUAL FUND MANAGER’S ATTRIBUTES IMPACT FUND PERFORMANCE? EVIDENCE FROM INDIA - Bhattacharjee, Kaushik; Yadav, Neetu; Singh, Geeta (Copernican Journal of Finance & Accounting, 2022)
This paper examines the impact of two managerial characteristics – qualification and work experience on the fund performance of various mutual fund schemes in India. We analyse 1508 fund managers during the period 2005–2018 using panel OLS regression. Our results suggest that work experience of the managers positively affects the performance of the open-ended schemes. After segregating the data into different schemes and different qualification categories, we find that the number of years, for which the manager is handling a scheme, is positively related to fund performance for almost all the schemes and qualifications. Further, we find evidence to support the notion that better quality of education and specialised courses also contribute to improving the fund performance. In India, the mutual fund industry is expected to grow at an exponential rate in the coming years, and this study provides an insight into the characteristics of the fund managers impacting the performance of such funds.